Utilization of Yard Land Through Horticultural Agriculture in Increasing Farmers' Income After the Covid-19 Pandemic in Cengkeh Turi Village, North Binjai District - Nadia Evira; Annio Indah Lestari Nasution; Siti Aisyah (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
This study aims to find out the background of the use of yards through horticultural farming so that it can increase farmers' income during a pandemic. This research is descriptive qualitative research, data collection methods are observation, interviews, and documentation. The subject of this study focused on 5 farmers with data analysis techniques using inductive thinking methods. The results showed that the use of yards through horticultural farming in Cengkeh Turi Village, North Binjai District could increase the income of farming families and was very helpful in improving the farmer's economy during the pandemic. This is proven by the farming families who live much better lives which are enough to meet their daily needs as seen from the salaries of the interviewees who have experienced an increase and jobs that are much lighter.